2008
DOI: 10.1111/j.1365-2672.2007.03687.x
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas–Acanthamoeba interaction and early shift to a viable but nonculturable state of Aeromonas by Acanthamoeba

Abstract: Aims: To investigate the hypothesis that amoeba may comprise a significant environmental reservoir for Aeromonas, Acanthamoeba-Aeromonas interaction experiments were performed. Methods and Results: Acanthamoeba were grown in monoculture and co-cultures with three different species of Aeromonas. Survival, invasion and viable but nonculturable state experiments were performed. We showed that at a low initial bacterial cell density, growth of Aeromonas spp. was inhibited by Acanthamoeba castellanii, while A. cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…aeruginosa and A. hydrophila where the cell counts exceeded 5 log cycles at time 0h with highly significant differences versus other bacterial strains (P <0.001 for both) and increased significantly in number to reach >8 and >7 log cycle at time 24h of co-incubation, respectively in comparison to other isolates (p <0.001 for both). The high multiplication rate of A. hydrophila inside FLA in our study has been demonstrated before [22,23]. Ps.…”
Section: Co-culture Of a Spelaea And Bacteriasupporting
confidence: 70%
“…aeruginosa and A. hydrophila where the cell counts exceeded 5 log cycles at time 0h with highly significant differences versus other bacterial strains (P <0.001 for both) and increased significantly in number to reach >8 and >7 log cycle at time 24h of co-incubation, respectively in comparison to other isolates (p <0.001 for both). The high multiplication rate of A. hydrophila inside FLA in our study has been demonstrated before [22,23]. Ps.…”
Section: Co-culture Of a Spelaea And Bacteriasupporting
confidence: 70%
“…The ability of P. aeruginosa to resist amoeba predation has been described by others (Wang & Ahearn, 1997), and it has been demonstrated recently that this lysis is related to necrosis and apoptosis, and mediated by the effect of type III secretion system effector proteins (Abd et al, 2008). The pathogenicity of P. aeruginosa in humans has been demonstrated to be associated with resistance to its lytic effect on amoebae (Fenner et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Survival of Aeromonas salmonicida has been observed in protozoa of the species Tetrahymena pyriformis (King & Shotts, 1988), and recently it has been demonstrated that free-living amoeba might play a role as a reservoir of Aeromonas spp. (Rahman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(235,242), has the capacity to multiply in the amoeba, and has cytopathic effects. The species Aeromonas hydrophila was found to interact actively with A. castellanii and to be able to survive within cysts (245,246).…”
Section: Fig 3 Amoeba Culturing Methods For Recovering Amoeba-resistimentioning
confidence: 99%